PRODUCTION OF LOW METHOXYL PECTIN AS AN ANTI CANCER AGENT FROM CITRUS PEEL PECTIN THROUGH ENZYME DEMETHYLATION BY PAPAYA PECTINESTERASE - Hartati, Indah; Riwayati, Indah; Kurniasari, Laeli (UMP, 2011)
Low methoxyl pectin (LMP) is reported posses anti cancer activity. LMP administering could reduce the risk of cancer, halt the progression of cancer, and in a certain percentage of cases caused the cancer cells to start to die. If this can be developed further, LMP administration could be a good co-treatment for chemotherapy or radiation. This would be a positive advancement, due to the high toxicity to the body of both chemotherapy and radiation. LMP can be produced by demethylation of high methoxyl pectin. One of our local resources that is potential for its pectin content is citrus peel. Pectin demethylation can be conducted by acid, alkali, ammonia in alcohol or enzymatic method. LMP produced by enzyme demethylation have been found to be inferior in quality to those produced by other methods. The enzyme took part in the pectin demethylation is pectinesterase. Pectinesterase can be be isolated from various source such as fruit and vegetables. One of our local resources that is potential as source of pectinesterase is papaya. Considering facts above thus it has a great possiblity to produce LMP from citrus peel pectin through enzymatic demethylation by utilize pectinesterase of papaya. Key-word : Low methoxyl pectin pectin (LMP), anti cancer, citrus peel pectin, papaya, pectinesterase